Rural Nurses' Research Use - Chad O'Lynn; Susan Luparell; Charlene A. Winters; Jean Shreffler-Grant; Helen J. Lee; Lori Hendrickx (Rural Nurse Organization; Binghamton University, 2009)
This descriptive study explored the availability of research findings to rural nurses and how they use those findings in clinical practice. Surveys were completed by 200 registered nurses located in the rural northern United States. The results indicate that research findings were available to most participants. The majority (82.9%) of participants agreed that changing practice based on research was beneficial; however, less than 40% of the respondents indicated that they would change their practice based on research findings if those findings contradicted previously-held knowledge, beliefs, intuition, or common sense. This study identifies a need for greater emphasis in the practice setting and in generic nursing education programs on the value and implementation of evidence based-practice.